Single High-Sensitivity Cardiac Troponin Measurement to Rule-out/Rule-in Myocardial Infarction in the Emergency Department - Anne Marie Dupuy; Yanis Gueche; Anne Sophie Bargnoux; Marion Morena; Bruno Lehodey; François Roubille; Jean Paul Cristol (The Journal of Applied Laboratory Medicine, 2026)
Abstract Background Point-of-care (POC) testing and triage liaison physicians could help alleviate the impact of emergency department (ED) overcrowding. The aim of our study was to evaluate the diagnostic performance of the TriageTrue POC assay for the rapid rule-out of myocardial infarction based on a single measurement of high-sensitivity cardiac troponin I (hs-CTnI). The diagnostic performance was compared to measurements obtained with the Vitros 3600 assay, taking into account the cutoffs recommended by the European Society of Cardiology. Methods The study compared results of troponin obtained simultaneously on the TriageMeterPro device from whole blood and plasma samples (n = 139) and the hs-cTnI assay on the Vitros 3600 instrument from EDTA plasma samples (n = 225). The diagnostic performance of the 3 methods was compared, including negative predictive value and sensitivity as well as positive predictive value and specificity. Concordance between the methods with disease state samples was then assessed using the Cohen kappa test. Results An excellent correlation between plasma and whole blood samples was achieved with the TriageTrue with a coefficient of correlation >0.99 and a bias of +8.2 (±45, with 95% CI 0.4 to 16.0) ng/L. A significant overestimation (around 47%) of the values obtained with the TriageTrue compared with those of the Vitros was also observed. Our results confirmed the acceptable and comparable diagnostic accuracy to the established hs-cTnI-Vitros assay, with a negative predictive value of 100% to rule-out myocardial infarction. Conclusion Our results demonstrated that the TriageTrue hs-cTnI whole blood test could serve as an alternative method for ruling out or confirming non-ST-elevation myocardial infarction in the prehospital setting using a single POC troponin measurement.